The Impact of Different Attentional Focus Strategies During Modeling on the Acquisition and Retention of Free Throws in Basketball - Rezaei, Marjansadat; Hatami, Farzaneh; Lotfi, Gholamreza (International Journal of Sport Studies for Health, 2023)
Background: In recent years, coaches and athletes have increasingly used observation as a tool for teaching and learning sports skills. Objectives: The aim of this study was to investigate the impact of modeling, using internal and external attentional focus strategies, on the acquisition and retention of free throw shooting in basketball. Methods: Forty-five female beginner basketball players (aged 21.62 ± 3.08 years, with a BMI of 23.48 ± 0.99 kg/m2) voluntarily participated in this study. Based on their pre-test scores using the ABBA method, they were divided into three groups: One group received modeling with an internal attention focus strategy, another group received modeling with an external attention focus strategy, and a control group. A video demonstrating the correct throwing technique was used to teach the attention-focusing strategies, and the groups did not receive any physical training. After watching the video, participants performed their own throwing attempts. Following group allocation, the participants entered the acquisition phase, which consisted of six sessions, with each session including two sets of ten attempts and a 2-minute rest period between sets. One-way analysis of variance was used for both immediate and delayed recall tests, and data analysis was conducted using SPSS 20 software.” Results: The study found a significant difference in free throw performance between the three modeling groups (internal attention focus, external attention focus, and control) during both the acquisition and delayed retention stages (P ≤ 0.05). Additionally, there was a significant difference in basketball free throw performance between the three modeling groups during the recall test (P ≤ 0.05). Conclusions: Overall, the results suggest that observational learning, combined with attentional focus strategies, is an effective method for improving skill acquisition and retention in basketball.